2017
DOI: 10.1111/jfr3.12288
|View full text |Cite
|
Sign up to set email alerts
|

Critical infrastructure impact assessment due to flood exposure

Abstract: Critical national infrastructures, including energy, transport, digital communications, and water, are prone to flood damage. Their geographical extent is a determinant of, and is determined by, patterns of human development, which is often concentrated in floodplains. It is important to understand how infrastructure systems react to large‐scale flooding. In this paper, we present an integrated framework for critical infrastructure flood impact assessment. Within this integrated framework, we represent interde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 22 publications
5
105
0
1
Order By: Relevance
“…The case of [9] builds on FEMA-HAZUS methodology [10] and follows a much more detailed analysis by using interdependencies but with the single problem of the huge requirement of data and the added difficulty of creating the network topology, and in most of the cases that information is confidential. Considering other methodologies as the proposed in [8] only the probability of flooding is assessed and not the probability of failure neither the economic losses. The most similar methodology can be found at [11] where a GIS-based approach is taken for the assessment of the electrical sector in flooding events determining the system exposure and vulnerability of the grid to flooding, with the particularity of not using fragility curves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of [9] builds on FEMA-HAZUS methodology [10] and follows a much more detailed analysis by using interdependencies but with the single problem of the huge requirement of data and the added difficulty of creating the network topology, and in most of the cases that information is confidential. Considering other methodologies as the proposed in [8] only the probability of flooding is assessed and not the probability of failure neither the economic losses. The most similar methodology can be found at [11] where a GIS-based approach is taken for the assessment of the electrical sector in flooding events determining the system exposure and vulnerability of the grid to flooding, with the particularity of not using fragility curves.…”
Section: Discussionmentioning
confidence: 99%
“…The most complete study found during the literature review was a GIS-based method assessing electrical grid and gas network through fragility curves focused on seismic events [7]. When focusing on flooding events a methodology to assess the flooding impact probability of the electrical assets was proposed in [8] where through spatial network models identified and compared the risk of critical infrastructures on flooded lands. Also, [9] proposed a method to investigate quantitatively the robustness of the grid against flooding events based on the Hazus methodology [10] providing a detailed risk analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The 3rd cascade would be that a blackout affects multiple other systems such as traffic lights, heating systems and so on. This notion is similar to studies separating the “asset scale” from the “network scale” (Dawson et al, ; Pant, Thacker, Hall, Alderson, & Barr, ). Whether these impacts are local or global depends very much on the context and should not be generalized; in one major city, all those infrastructures may exist within city boundary and are run by local companies, in another city and country, effects could cascade cross‐national boundaries.…”
Section: Framework For Critical Infrastructure Resilience and Cascadimentioning
confidence: 99%
“…Wastewater disruptions may first seem local, but when affected by certain unknown bacteria, could affect other systems, sectors or regions downstream. Temporal cascades are important to separate; some failures impact within seconds, others in hours or days; see previous applications of the CQs such as temporal aspects (Fekete, Lauwe, & Geier, ; Pant et al, ). While this separation is still within the same comparable, often linear scale metric, it is important to outline other temporal cascades when time‐lag effects and irregular patterns occur such as a slowly disintegrating power line coating failing hours after the initial power failure, which often brings the second crash to a system just about recovering and then crashing it more severely.…”
Section: Framework For Critical Infrastructure Resilience and Cascadimentioning
confidence: 99%
“…Pant et al (this issue) show how impacts on critical infrastructure propagate to significant effects outside the flood zone. This is where the spatial dimension of urban areas with their infrastructure can play a substantial role for flood losses.…”
Section: Urban Resiliencementioning
confidence: 99%